Equilibrium real interest rates for the BRICS countries - Jens Klose (Philipps-University Marburg, School of Business and Economics, 2018)
The equilibrium real interest rate is one of the most discussed variables in economics, although it is unobservable. While it has been estimated with respect to various developed countries, this paper is the first to estimate it for five developing countries - the BRICS countries. To do so the most widely used model in this respect - the Laubach and Williams model - is used. Moreover, the results are compared to the actual real interest rate to give an indication whether e.g. monetary policy was too tight or too loose in certain periods. The results indicate that we indeed have substantial differences between the actual and the equilibrium real interest rate going either way. While for China and India monetary policy tends to be too loose in many periods, thus boosting economic growth even further, the reverse seems to be true with respect to Brazil especially in the late 1990s and the beginning of the 2000s. In Russia and South Africa the actual real rate is mainly in line with the equilibrium one, thus monetary policy is neither to loose nor too tight.
Keywords: E43; F45; C32; 330; equilibrium real interest rate; BRICS; state-space-models